Enterprise Composite Blockchain Double Layer Consensus Algorithm Based on Improved DPoS and BFT - Li, Su; Zhang, Haolin; Chen, Ze; Wang, Junlu; Song, Baoyan (Peer-to-peer networking and applications, 2024)
The consensus mechanism serves as the fundamental technology behind blockchain, enabling the establishment of a decentralized and reliable network system that achieves consensus among nodes without relying on the trustworthiness of individual nodes. In the enterprise composite blockchain, the master chain adopts a licensed public chain. However, existing consensus mechanisms cannot be directly applied to the licensed public chain. To address this, this paper proposes a dual-layer consensus algorithm that combines DPoS and PBFT. Aiming at the problem that DPoS voting mechanism commonly elects the node holding more tokens, which can lead to issues of political indifference. On the other hand, PBFT suffers from concerns such as inflexible and singular master node election, high communication complexity during the consensus process, and substantial overhead associated with view changes. In light of these challenges, this paper introduces an improved DPoS and BFT-based double-layer consensus algorithm designed specifically for the enterprise composite blockchain. Initially, the algorithm votes to generate a set of consensus nodes by improved DPoS verification pool selection. Subsequently, the elected consensus nodes generate blocks and conduct on-chain operations using a BFT consensus algorithm that integrates VRF and TS. Through experimental verification, this paper proposed algorithm effectively enhances system security and node activity without sacrificing usability. Moreover, comparative analysis against existing algorithms demonstrates higher transaction throughput, lower transaction latency, and reduced CPU load associated with this paper proposed algorithm.